Dampak Perceraian Bagi Perkembangan Anak - Faizal; Hadid Nabil Bayhaqy (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Divorce cases are not only detrimental to several parties involved, such as the husband, wife, parents of each partner, and children, but are also an act that is hated by Allah SWT. Unfortunately, the divorce rate, especially in Indonesia, continues to increase from year to year. Children are the people who feel the impact of their parents' divorce the most. For a child to grow and develop, he needs love from a complete, conducive family. Parents are the first and foremost place of education for children. Apart from that, parents are also an important foundation for the development of their children. Parents are the place to spend most of the time in their children's lives. When parents start to conflict, even choose to divorce, the child is the first victim who will feel the psychological and mental impact.